Spontaneous coronary artery dissection associated with incidental finding of left ventricular thrombus - Melvin Santana; Nirmal Guragai; Biren Patel; Rahul Vasudev; Preet Randhawa; Meherwan Joshi; Habib Mirette; Fayez Shamoon (Greater Baltimore Medical Center, 2021)
Spontaneous Coronary Artery Dissection (SCAD) is one of the nonatherosclerotic causes of Acute Coronary Syndrome. It's extremely rare for SCAD to present in an asymptomatic male, with incidental finding of Left Ventricular (LV) thrombus on echocardiogram. This report presents the case of a 36-year-old male with such an atypical presentation of Spontaneous Coronary Artery Dissection with Left Ventricular apical thrombus as a complication. The patient received successful medical management, with excellent clinical outcomes. This case highlights the importance of an early recognition and treatment strategy for both conditions using medical therapy.